2020
DOI: 10.3389/fgene.2020.575012
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Animal Susceptibility and Therapeutic Drugs to SARS-CoV-2 Based on Spike Glycoprotein Combined With ACE2

Abstract: Recently, a few animals have been frequently reported to have been diagnosed with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Whether they are SARS-CoV-2 intermediate hosts is worthy of great attention. The interaction of SARS-CoV-2 spike protein and its acceptor protein ACE2 is an important issue in determining viral host range and cross-species infection, while the binding capacity of Spike protein to ACE2 of different species is unknown. Here, we used the atomic structure model of SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(36 reference statements)
1
8
0
2
Order By: Relevance
“…Among feline species, the amino acid sequence of ACE2 is highly conserved, and human and feline ACE2 share a homology of 85% in total and 80% referring to the residues involved in SARS-CoV-2 attachment ( Supplementary Material Figure S1a ). In consistence with previous studies [ 32 , 33 , 34 ], we showed that feline ACE2 is capable of mediating SARS-CoV-2 S-driven entry as efficiently as human ACE2. Investigations on the expression levels of ACE2 within the respiratory tract of felids revealed that the highest amounts of ACE2 mRNA and protein were detected in nasal mucosa, whereas only limited expression was observed in lung tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Among feline species, the amino acid sequence of ACE2 is highly conserved, and human and feline ACE2 share a homology of 85% in total and 80% referring to the residues involved in SARS-CoV-2 attachment ( Supplementary Material Figure S1a ). In consistence with previous studies [ 32 , 33 , 34 ], we showed that feline ACE2 is capable of mediating SARS-CoV-2 S-driven entry as efficiently as human ACE2. Investigations on the expression levels of ACE2 within the respiratory tract of felids revealed that the highest amounts of ACE2 mRNA and protein were detected in nasal mucosa, whereas only limited expression was observed in lung tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the structures of SARS-CoV-2, 3C-like (3CL) protease hydrolase has been identified as a potential target against COVID-19, because it can inhibit the replication of CoV [ 13 ]. Meanwhile, angiotensin-converting enzyme 2 (ACE2) has a great affinity with the spike protein of SARS-CoV-2[ 14 ]. Therefore, ACE2 and 3CL were considered as receptors in molecular docking.…”
Section: Introductionmentioning
confidence: 99%
“…A structural analysis identified 20 residues of the human ACE2 receptor that contact the SARS-CoV-2 spike protein receptor binding domain; members of the Felidae share 16 out of the 20 contacting residues [173]. Another structural analysis of the ACE2 receptor identified 13 binding domain contacting residues of the human ACE2 receptor; domestic cats share 12 of these 13, and they also share with humans 14 of the 15 hydrogen bonds at the SARS-CoV-2 RBD/ACE2 interface [174]. A third study reported 14 human ACE2-contacting residues with both domestic cats and tigers sharing 11 of the 14 [175].…”
Section: The Felidaementioning
confidence: 99%